An Analysis Of Employee Knowledge With A Safety Behavior Approach In Kendari Ocean Fisheries Industrial Area: Knowledge With A Safety Behavior - Noviati Noviati; Abdul Rahim Sya`ban; Toto Surianto S (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Objectives: Development in Indonesia is so rapid in various fields, including the industrial sector, services, property, mining, transportation, and others. However, behind this progress there is a price that must be paid by the people of Indonesia, namely the negative impact it causes in the form of disasters, accidents, pollution, and occupational diseases that result in thousands of people being injured every year. Methods: This study uses a mixed method. The population in this study was selected from 3 companies using the random sampling method, namely, selecting subjects from the target sub-population using a random procedure so that the number obtained was 488 people, with a total sample of 83 people. Results: The results obtained indicate that there is a relationship between knowledge and safety behavior in the Kendari Ocean Fishing Port Industrial Area, with a calculated X2 value of 16,419. Conclusion: Management needs to increase positive reinforcer factors, for example, by giving awards in the form of praise, gifts, promotions, and so on, because behavior change tends to be easier if individuals benefit from changing their behavior.